2016
DOI: 10.1007/s11934-016-0589-z
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging-Ultrasound Fusion-Guided Prostate Biopsy: Review of Technology, Techniques, and Outcomes

Abstract: Transrectal ultrasound (TRUS)-guided (12–14 core) systematic biopsy of the prostate is the recommended standard for patients with suspicion of prostate cancer (PCa). Advances in imaging have led to the application of magnetic resonance imaging (MRI) for the detection of PCa with subsequent development of software-based co-registration allowing for the integration of MRI with real-time TRUS during prostate biopsy. A number of fusion-guided methods and platforms are now commercially available with common element… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(30 citation statements)
references
References 68 publications
0
29
0
1
Order By: Relevance
“…reported that the cancer detection rate for transrectal targeted biopsy using the UroNav system was significantly higher at 48.1% (39/81 patients) than for transrectal biopsy with visual registration at 34.6% (52/150 patients; P = 0.04) or 12‐core transrectal systematic biopsy at 32% (32/100 patients; P = 0.03) . The Urostation system (Koelis, Meylan, France) uses elastic fusion and 3‐D TRUS image needle tracking . Mozer et al .…”
Section: Discussionmentioning
confidence: 99%
“…reported that the cancer detection rate for transrectal targeted biopsy using the UroNav system was significantly higher at 48.1% (39/81 patients) than for transrectal biopsy with visual registration at 34.6% (52/150 patients; P = 0.04) or 12‐core transrectal systematic biopsy at 32% (32/100 patients; P = 0.03) . The Urostation system (Koelis, Meylan, France) uses elastic fusion and 3‐D TRUS image needle tracking . Mozer et al .…”
Section: Discussionmentioning
confidence: 99%
“…The targeted biopsy of mpMRI suspicious areas could be performed using "in-bore" mpMRI-guidance, real-time mpMRI/TRUS imaging fusion or by performing cognitive mpMRI/TRUS biopsies (29,30). Recently, many papers have demonstrated a higher accuracy in favour of the fusion technique; conversely, few data have been reported regarding the accuracy of TR vs. TP mpMRI/TRUS fusion approach in diagnosing clinically significant PCa (12,13). In this respect, standard TP and TR prostate biopsies are provided of a superimposable detection rate for PCa (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17), but, at the same time, the transperineal approach allows to easily and better reach the anterior zone of the gland (15) resetting the risk of sepsis (16).…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, multiparametric magnetic resonance imaging (mpMRI) combined with TRUS (transrectal ultrasound) fusion targeted biopsy has improved the accuracy of standard biopsy schemes in detecting clinically-significant prostate cancer (PCa), especially, in case of a repeat biopsy (5-7) and in the reevaluation of men enrolled in active surveillance (AS) programs (8)(9)(10). Although the accuracy of mpMRI/fusion targeted biopsy has been evaluated in a lot of series, very few papers have compared the detection rate for PCa or/and complications of the different MRI/TRUS fusion platforms in the same population (11)(12)(13)(14). On the other hand, the standard transperineal biopsy approach in comparison with the transrectal procedure has demostrated a higher accuracy in diagnosing PCa located in the anterior zone of the gland (15) resetting the risk of sepsis (16).…”
mentioning
confidence: 99%
“…This is employed by devices such as UroNav ® , Real-Time Virtual Sonography (RVS) (Hitachi, Tokyo, Japan), Virtual Navigator ® (Esaote, Florence, Italy), and BK Fusion ® (Analogic, Peabody, MA, USA) (20,(22)(23)(24)(25). Alternatively, the Artemis System ® (Eigen, Grass Valley, CA, USA), Biojet ® (DK Technologies, Barum, Germany), Fusion Bx (Focal Healthcare, Toronto, Canada) and Biopsee ® (Oncology Systems Limited, Shropshire, England) use a different registration technique that incorporates a mechanical arm with encoded joints attached to the ultrasound probe to report movement and feedback to the system (20,(26)(27)(28)(29). One last modality to register location is realtime ultrasound feedback which uses the initial ultrasound scan to re-create the prostate 3D model and track the needle based solely on ultrasound images (20,28).…”
Section: Workflow For Fusion Biopsymentioning
confidence: 99%